Comparison Of Health-seeking Behaviour Between Urban And Rural Malay Population Of Negeri Sembilan, Malaysia - Mohd Dzulkhairi Mohd Rani; Muslimah Ithnin; Norsham Juliana; Nadia Mohd Effendy; Sahar Azmani; Khadijah Hasanah Binti Abang Abdullah; Muhammad Shamsir Mohd Aris; Izuddin Fahmy Abu; Nadeeya'ayn Umaisara Mohamad Nor (JK Welfare & Pharmascope Foundation, 2024)
Indexed by Scopus